2022
DOI: 10.3390/cancers14082020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Tumor Treating Fields with Pemetrexed and Platinum-Based Chemotherapy for Unresectable Malignant Pleural Mesothelioma: Single-Center, Real-World Data

Abstract: Purpose: The objectives of this study were to evaluate the implementation, device usage rates, clinical outcomes, and treatment-related toxicities associated with TTFields and pemetrexed plus platinum-based chemotherapy in patients with unresectable MPM, outside the initial trial results. Methods: Consecutive patients with unresectable MPM were enrolled onto an FDA-required HDE protocol from 2019 to 2021. All patients were treated with a protocol-defined regimen of continuous TTFields (150 kHz) and pemetrexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The most common types are contact dermatitis, pruritus, hyperhidrosis, pressure necrosis, and skin erosions (Figure 2; Supplementary Figure S1). Findings from clinical studies have demonstrated that most skin AEs are mild and manageable without the need to significantly disrupt treatment (3,4,10), which is supported by real-world data (17,26). Although analysis of skin AEs from pilot studies has not identified any correlation between select risk factors and the occurrence of TTFields therapy-related skin AEs (Table 1), several factors may increase the risk and severity of skin damage.…”
Section: Ttfields Therapy-associated Skin Aesmentioning
confidence: 91%
See 1 more Smart Citation
“…The most common types are contact dermatitis, pruritus, hyperhidrosis, pressure necrosis, and skin erosions (Figure 2; Supplementary Figure S1). Findings from clinical studies have demonstrated that most skin AEs are mild and manageable without the need to significantly disrupt treatment (3,4,10), which is supported by real-world data (17,26). Although analysis of skin AEs from pilot studies has not identified any correlation between select risk factors and the occurrence of TTFields therapy-related skin AEs (Table 1), several factors may increase the risk and severity of skin damage.…”
Section: Ttfields Therapy-associated Skin Aesmentioning
confidence: 91%
“…The most common adverse events (AEs) associated with TTFields therapy are dermatologic AEs, as reported in both clinical studies and recent real-world data ( 7 , 9 12 , 14 , 17 ). Advice on the prevention and management of dermatologic scalp AEs associated with TTFields therapy are available; however, no such guidance exists for the thoracic region, which is especially needed as skin AEs in the thoracic region are often exacerbated from the motion of respiration ( 18 ).…”
Section: Introductionmentioning
confidence: 93%
“…TT Fields at a frequency of 150 kHz exhibited the highest cytotoxicity to mesothelioma cells, led to an enhanced number of DNA double-strand breaks, and diminished expression of Fanconi Anemia (FA)-BRCA DNA repair pathway proteins. The co-treatment of TT Fields with cisplatin or pemetrexed significantly enhanced treatment efficacy (56,57). Nevertheless, there are a few limitations of the STELLAR study that should be mentioned.…”
Section: Local Therapiesmentioning
confidence: 99%
“…This process takes place both in normal (healthy) and cancer cells [ 53 ]. This drug has found application in the treatment of lung (NSCLC) and pleura (mesothelioma) cancers [ 53 , 54 ]. The nephrotoxic effect has its pathomechanism in inducing stromal fibrosis, interstitial edema, and vacuolization of proximal tubular cells with the retained glomerular structure [ 13 , 55 , 56 ].…”
Section: Chemotherapymentioning
confidence: 99%